Modeling Optimal Fiscal Consolidation Paths in a Selection of European Countries - Kanda, Daniel (Washington, D.C. : International Monetary Fund, 2011)
For a number of countries - Italy, Netherlands, the United Kingdom, Germany, Ireland, and France - this paper develops an inter-temporal model that elicits the implied country-preferences over balancing the conflicting objectives of fiscal consolidation and reduction of economic slack. The model suggests that some front-loading of adjustment is desirable, although the extent would vary by country preferences. It also finds that proposed consolidations may prove to be stronger than acceptable, especially if somewhat larger than anticipated fiscal multipliers lead to a sizeable economic deceleration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet